2011
DOI: 10.1136/ard.2011.153569
|View full text |Cite
|
Sign up to set email alerts
|

ANCA-associated vasculitis is linked to carriage of the Z allele of α1 antitrypsin and its polymers

Abstract: The Z but not the S deficiency allele is associated with AAV. Polymers of α1AT are present in the serum and glomeruli of at least some patients with the Z allele, which may promote inflammation through priming of neutrophils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 36 publications
2
34
0
Order By: Relevance
“…Of the many polymorphisms of AAT, the Z and S alleles are responsible for most α1-antitrypsin deficiency cases. Increased frequency of heterozygosity for the Z and S alleles in association with GPA, but not MPA, has been reported by several groups in small studies and recently confirmed in larger studies [46,47]. The clinical significance of this association is not entirely clear, but heterozygosity for the Z allele has been associated with a worse prognosis of the disease [48].…”
Section: Genetic Predispositionmentioning
confidence: 79%
See 1 more Smart Citation
“…Of the many polymorphisms of AAT, the Z and S alleles are responsible for most α1-antitrypsin deficiency cases. Increased frequency of heterozygosity for the Z and S alleles in association with GPA, but not MPA, has been reported by several groups in small studies and recently confirmed in larger studies [46,47]. The clinical significance of this association is not entirely clear, but heterozygosity for the Z allele has been associated with a worse prognosis of the disease [48].…”
Section: Genetic Predispositionmentioning
confidence: 79%
“…This may be because Z allele carriers, but not S allele carriers, have increased levels of pro-inflammatory polymers circulating in their blood [47]. Deposits of these polymers have been documented in kidney biopsy specimens from patients with active GPA, and these polymers can prime neutrophils and augment the activation of neutrophils by PR3-ANCA in vitro [47].…”
Section: Genetic Predispositionmentioning
confidence: 97%
“…We have also recently shown that H 2 S can inhibit airway smooth muscle cell proliferation and inflammatory mediator release in vitro [3]. Serum levels of H 2 S positively correlate with the decline in lung function in chronic obstructive pulmonary disease (COPD) and were significantly lower in Global Initiative for Chronic Obstructive Lung Disease (GOLD) stage III patients compared with those in GOLD I [4]. Existing therapies for COPD, such as corticosteroids or long-acting anticholinergic agents, may reduce the exacerbation rate but do not significantly slow disease progression.…”
Section: To the Editormentioning
confidence: 99%
“…Polymers of a 1 -antitrypsin form within the lung as a result of local inflammation and exposure to cigarette smoke [2]. They have also been identified in the skin of an individual with a 1 -antitrypsin deficiency and panniculitis [3] and in a renal biopsy from an individual with a 1 -antitrypsin deficiency and vasculitis [4]. It is unknown whether these polymers form locally or are deposited in these tissues from a circulating source, and whether extrahepatic polymers are associated with any disease phenotypes.…”
Section: To the Editormentioning
confidence: 99%
“…2 In particular, section 3.2.2 on page 822 details the interaction of this disease with environmental, mainly infectious factors. However, in limiting the scope of literature considered, we feel that another lesser but important association with alpha-1 antitrypsin deficiency (AATD) has been omitted from this review and which also has resulted in a systematic blind-spot in the general hepatology literature.…”
Section: Editorsmentioning
confidence: 99%